2013
DOI: 10.3389/fnins.2013.00123
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in children born preterm—role of exposure to perinatal inflammation

Abstract: Autism Spectrum Disorder (ASD) is the collective term for neurodevelopmental disorders characterized by qualitative impairments in social interaction, communication, and a restricted range of activities and interests. Many countries, including Australia, have reported a dramatic increase in the number of diagnoses over the past three decades, with current prevalence of ASD at 1 in every 110 individuals (~1%). The potential role for an immune-mediated mechanism in ASD has been implicated by several studies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 181 publications
(177 reference statements)
1
25
0
1
Order By: Relevance
“…45 However, other factors associated with both LMPT birth and ASD may account for this relationship, including advanced maternal age, induction of labor, perinatal inflammation, and preeclampsia. 13,46,47 Given the small number of infants with true positive screens, we were unable to carry out multivariable analyses to adjust for factors that may confound the relationship between ASD and LMPT birth. Where we explored potential associations using univariate analyses, no factors were significantly associated with true positive screens.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, other factors associated with both LMPT birth and ASD may account for this relationship, including advanced maternal age, induction of labor, perinatal inflammation, and preeclampsia. 13,46,47 Given the small number of infants with true positive screens, we were unable to carry out multivariable analyses to adjust for factors that may confound the relationship between ASD and LMPT birth. Where we explored potential associations using univariate analyses, no factors were significantly associated with true positive screens.…”
Section: Discussionmentioning
confidence: 99%
“…Autism is a neurodevelopmental disorder that has been associated with several genetic variants and with environmental factors originating with the mother and the child. Several studies suggest that maternal infections or disruptions in the immune system during the pre‐/perinatal period may increase risk of autism [Brown et al, ; Lee et al, ; Meldrum et al, ; Zerbo et al, ]. Given the effects of congenital Toxoplasma gondii ( T. gondii ), an intracellular parasite, on early brain development [Berrebi et al, ; Roizen et al, ; Swisher et al, ], the infection is a viable prenatal exposure to study in relation to risk of autism.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a small but growing body of studies suggests that children born VPT are subject to a range of social and behavioral difficulties that may affect their life‐course opportunities . Several contemporary follow‐up studies have also found an increased risk of autism spectrum disorders and related behaviors in survivors of VPT birth . Although suggestive of a possible link between prematurity and later social problems, the interpretation of existing research has been limited by several methodological problems.…”
mentioning
confidence: 99%
“…[12][13][14] Several contemporary follow-up studies have also found an increased risk of autism spectrum disor-ders and related behaviors in survivors of VPT birth. [15][16][17] Although suggestive of a possible link between prematurity and later social problems, the interpretation of existing research has been limited by several methodological problems. First, there is considerable variability across studies in the outcomes assessed.…”
mentioning
confidence: 99%